Mga saloobin at motibasyon ng mga estudyanteng Muslim ng MSU-SuluCollege of Technology and Oceanography Preparatory High School sa Pilipino bilang wikang panturo - Elumba, Josephine G. 1946- (1979)
This research aimed to determine the attitudes of Muslim students (Samal and Tausug) of Mindanao State University-Sulu Colloge of Technology and Oceanography Preparatory High School toward the use of Filipino as a medium of instruction. Two kinds of questionnaires were used as the instrument for gathering data for the study: the questionnaire for the attitude towards the use of Filipino as medium of instruction; and the questionnaire towards the speakers of Samal and Tausug and speakers of Filipino. The author pointed out that since it has became mandatory for the students/teachers who are in a second language environment to learn Filipino with the implementation of bilingual policy in our country, two aspects should be given attention to this bilingual program: the attitude and motivation of the students.
Appendices: leaves 99-151
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Education, Bilingual -- Philippines; Bilingualism -- Psychological aspects. -- Philippines; Pilipino language